CHRONOLOGICAL FRAMEWORK FOR THE LATEGLACIAL POLLEN AND MACROFOSSIL SEQUENCE IN THE PIRIN MOUNTAINS, BULGARIA: LAKE BESBOG AND LAKE KREMENSKO-5 - Stefanova I.; Atanassova Ju.; Delcheva M.; Wright H.E. (My University, 2006)
The sediments of numerous cirque lakes in the Pirin Mountains have yielded several generalized pollen diagrams, but low stratigraphic and temporal resolution has hampered detailed reconstruction of the vegetational history, especially for the Lateglacial. New pollen and macrofossil analyses of high stratigraphic resolution combined with well-controlled time-depth curves for Lake Besbog and Lake Kremensko-5 now permit the firm identification of the Lateglacial interstadial interval (BOlling-AllerOd), dated at 13.8-12.6 ka cal. BP at Besbog and 14.1-12.8 ka cal. BP at Kremensko-5 and correlated with the Greenland Interstadial GI-1 (14.5-12.6 ka cal. BP). Macrofossil analyses indicate that during the BOlling-AllerOd period Betula and Juniperus occurred around the lakes (at 2124-2250 m a.s.l). Following the Younger Dryas a Betula woodland covered the mountains between 1900 and 2250 m in the early Holocene. Because of higher summer insolation at this time, the temperate deciduous forest reached up to 1900 m, or 800 m above their present limit, producing a regional pollen rain that dominated pollen deposition in the cirque lakes. After about 7000 cal. yr BP conifer forests replaced the birch woodland at middle and high elevations.
Keywords: VEGETATION HISTORY; LATEGLACIAL CHRONOLOGY; HOLOCENE; MACROFOSSILS; PIRIN MOUNTAINS; BULGARIA; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен